2020
DOI: 10.1590/1980-265x-tce-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Practices for the Prevention of Sexually Transmitted Infections Among University Students

Abstract: Objective: to analyze the sexual practices adopted by university students for the prevention of Sexually Transmitted Infections Method: a quantitative, descriptive and cross-sectional study, conducted in 2016, at a private university in the municipality of Rio de Janeiro, Brazil. A convenience sample was selected, stratified by gender, of 768 students who answered a self-administered questionnaire, structured with variables of sociodemographic characterization and related to knowledge about sexually transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…Tal fato pode estar associado à rede social da primeira semente da técnica de snowball e, dessa forma, os resultados deste estudo podem apresentar um viés racial. 2,8,19 No que diz respeito à compreensão dos homens universitários sobre as infecções de transmissão sexual, os participantes entendem que existem microrganismos que causam as IST, porém sem um esclarecimento sobre quais são eles, seus principais sinais e sintomas. Para além do entendimento de que existe uma infecção que é causada por "vírus, bactérias, fungos e microrganismos" (E18), é essencial a orientação sobre quais são e sobre quais os seus principais sinais e sintomas, para a identificação e a busca oportuna de atendimento em saúde.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Tal fato pode estar associado à rede social da primeira semente da técnica de snowball e, dessa forma, os resultados deste estudo podem apresentar um viés racial. 2,8,19 No que diz respeito à compreensão dos homens universitários sobre as infecções de transmissão sexual, os participantes entendem que existem microrganismos que causam as IST, porém sem um esclarecimento sobre quais são eles, seus principais sinais e sintomas. Para além do entendimento de que existe uma infecção que é causada por "vírus, bactérias, fungos e microrganismos" (E18), é essencial a orientação sobre quais são e sobre quais os seus principais sinais e sintomas, para a identificação e a busca oportuna de atendimento em saúde.…”
Section: Discussionunclassified
“…O conhecimento também possibilita ao jovem reconhecer as infecções assintomáticas e a necessidade de utilização do preservativo e/ou uso de outras tecnologias de prevenção, como a ida regular a serviços de saúde. [7][8][19][20] Com relação ao conhecimento sobre as principais formas de transmissão das IST, o estudo evidencia que os jovens têm ciência, inclusive fazem apontamentos sobre os comportamentos de risco e sexo desprotegido. Porém, a transmissão vertical só foi abordada por um participante.…”
Section: Discussionunclassified
“…In Brazil, a quantitative study carried out with 768 young people from a private university in Rio de Janeiro observed that 85.16% of the participants had an active sex life, of which 62.54% did not use condoms in all their sexual activities. Moreover, 84.83% said they had sexual intercourse with a steady partner, of which 44.01% used condoms, and 47.86% had sex with casual partners, of which 63.58% reported using condoms (Ramos et al, 2020). STI prevention is the main reason why young people use condoms with casual sexual partners (Darré et al, 2018;Gutierrez et al, 2019;Nascimento et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Sexually transmitted infections (STIs) are responsible for several conditions that compromise individuals' quality of life and sexual and reproductive health during all stages of the life cycle (World Health Organization [WHO], 2016). STIs are among the most common acute conditions worldwide, particularly among young adults (Ramos et al, 2020). STIs also indirectly favor the sexual transmission of the Human Immunodeficiency Virus (HIV) and can lead to cellular changes, which precede some types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Com o ingresso no ensino superior, os jovens enfrentam novos desafios e se deparam com situações que moldam seus valores (Perim et al, 2020;Ramos et al, 2020). O ingresso em uma universidade traz à tona sensações e emoções que reforçam o conceito ilusório de autoreflexo de invulnerabilidade da juventude, e pode ser visto por meio de uma maior liberdade sexual que expõe os jovens a comportamentos de risco para a saúde e maiores riscos à aquisição de IST (Pimentel, 2016;Graf;Mesenburg;Fassa, 2020).…”
Section: Introductionunclassified